ANALYSIS OF MERGERS, ACQUISITIONS’ IMPACT ON ITS FINANCIAL PERFORMANCE (Case Study on Listed Companies in Indonesia Stock Exchange) - Putri, Vonny (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The research aims to know the impact of mergers, acquisitions on the financial performance and to know the difference in company performance before and after mergers, acquisition by its financial ratio. To reveal how big the impact of the mergers, acquisitions to the financial performance, the paired sample t-test used to prove its analysis. This research is categorized into an event study.There are as many as 21mining companies listed in IDX and the author used 10 companies as sample in this study. The data collection technique used was a documentation method, which is documented by records or took the financial satements of companies listed in IDX. The sample selection used purposive sampling technique which is a random type of sample determination achieved by considering certain criteria, mainly adjusted to the research objectives or problems. The research instruments are tested by event window, statistical analysis and descriptive analysis. To analyze the data, the paired sample t-test was used. The research resultshows that there is no significant impact of mergers, acquisitions on the financial performance and the difference on companies’ performance before and after mergers, acquisition lies on the greater mean of liquidity and activity ratio after mergers, acquisition, and the decreasing value of leverge and profitability ratio. Keywords: mergers, acquisitions, financial ratio